1962
DOI: 10.1113/expphysiol.1962.sp001606
|View full text |Cite
|
Sign up to set email alerts
|

The Nephropathy of Experimental Potassium Deficiency. An Electron Microscopic Study

Abstract: The most prominent abnormality in renal function in potassium depletion in man and in experimental animals is a defect in concentrating power. Although it has been suggested that in rats this may be due to lesions in the collecting tubules, the virtual absence of these histological abnormalities in human material and in dogs is paradoxical. In the experiments reported here, mild potassium depletion has been induced in rats by dietary restriction and the kidneys of these animals examined by the electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1964
1964
1991
1991

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…While firm conclusions cannot be drawn regarding the functional significance of these changes, the alteration in tubular basement membrane which can be induced by hydration is almost certainly associated with changes in permeability which are likely to effect the counter-current mechanism. Similar but less marked changes in the basement membrane of some of the thin segments of the loop of Henle have recently been reported in rats undergoing saline diuresis and in potassium-depleted animals [Lapp and Nolte, 1962;MacDonald et al, 1962]. Electron microscopy of medulla from dehydrated animals did not reveal any structures in the collecting ducts corresponding to the "pores" described by Ginetsinsky.…”
supporting
confidence: 81%
“…While firm conclusions cannot be drawn regarding the functional significance of these changes, the alteration in tubular basement membrane which can be induced by hydration is almost certainly associated with changes in permeability which are likely to effect the counter-current mechanism. Similar but less marked changes in the basement membrane of some of the thin segments of the loop of Henle have recently been reported in rats undergoing saline diuresis and in potassium-depleted animals [Lapp and Nolte, 1962;MacDonald et al, 1962]. Electron microscopy of medulla from dehydrated animals did not reveal any structures in the collecting ducts corresponding to the "pores" described by Ginetsinsky.…”
supporting
confidence: 81%
“…ANP has been shown to induce significant kaliuresis along with natriuresis (DeBold et al, 1981;Seymour et al, 1985). This effect may involve intercalated cells because several studies have demonstrated hypertrophy and increased numbers of intercalated cells in the outer medullary collecting ducts of hypokalemic or waterdeprived rats (Oliver et al, 1957;MacDonald et al, 1962;Hancox and Komender, 1963;Kennedy and Parker, 1963). The hypertrophic response included a transfer of membrane from apical vesicles to the luminal surface ofthe cell (Stetson et al, 1980;Brown et al, 1987) and was correlated with decreased urine-concentrating ability in K + -deficient animals.…”
Section: Discussionmentioning
confidence: 92%
“…A significant proportion of them, how ever, tended to sequester cytoplasmic components and appeared to be cytosegrosomes [27], One of the conspicuous constituents of these cytosegrosomes were ribosome-like particles. We could not ascertain whether some of the droplets were of mitochondrial origin [28], However, an elaborate membrane system was the sole constituent of several droplets. Many droplets appeared to be in the process of enlargement not only by fusing with each other, but also by incorporating cytoplasmic material through a gap in the discontinuous limiting membrane.…”
Section: Medullamentioning
confidence: 99%